Morphologic variation in the genus Astraeus (Boletales, Basidiomycota in relation with geographical and climatic conditions in the Chihuahua and Sonora mountain islands, Mexico - Valero Galván, José; Botello-Camacho, Alejandro; González-Fernández, Raquel; Pérez-Calderón, José Ricardo (Acta Universitaria, 2015)
The Mountain Islands are characterized by climatic conditions and the height above mean sea level differs significantly from those found in the middle plains. This condition certain species distribution to the highest parts of the mountains limiting gene flow between populations. Where the desert plains act as geographical barriers. The objective of this research was to analyze the morphological variation in the genus Astraeus in states of Chihuahua and Sonora mountain islands. Specimens were collected from eight locations, recording the geographic data from each one. Measurements of rays number, diameter of exoperidium, endoperidium and spores of each specimen were performed. A variance and hierarchical analysis were conducted to establish groups of populations. These analysis showed a close relation between La Escondida and La Boquilla populations with Norogachi and Cueva de la Olla. These populations showed a tendency to join in the same group. In the contrary, Sierra La Amargosa and San Luis populations, showed a close relation to cluster with Cananea and Sierra Peñascos. Which, were the most phylogenetically related populations. A correlation between latitude and the number or rays, and a correlation between the endoperidium diameter and the minimal precipitation of the driest month was found.